Factors associated with young people's attendance at an IPV prevention intervention in informal settlements in South Africa: A prospective analysis. Issue 2 (1st February 2020) - Gibbs, Andrew; Dunkle, Kristin; Washington, Laura; Sikweyiya, Yandisa; Willan, Samantha; Shai, Nwabisa; Jewkes, Rachel
ABSTRACT: Understanding factors shaping attendance at behavioural interventions is critical for programmatic planning. Through the Stepping Stones and Creating Futures intervention trial amongst young (18-30) women and men to reduce intimate partner violence and strengthen livelihoods, we prospectively assessed factors associated with intervention attendance. Baseline data were collected between September 2015 and September 2016 among 677 women and 675 men. For women, in multinomial models, compared to high attenders, medium ( β  = −0.04, p  = 0.001) and low ( β  = −0.05, p  = 0.003) attenders had lived less time in the community, medium attenders were more likely to have children ( β  = 0.97, p  = 0.001), and low attenders had less gender-equitable attitudes ( β  = −0.57, p  = 0.035). For men, in multinomial models, compared to high attenders, medium attenders were more likely to have completed secondary school ( β  = 1.48, p  = 0.011) and to have worked in the past three months ( β  = 0.64, p  = 0.021). Low attenders had lived for a shorter period in the community ( β  = −0.06, p  = 0.005), and were more likely to have worked in the past three months ( β  = 0.66, p  = 0.041) compared to high attenders. Attendance was shaped by structural factors, and gender-specific factors, and these need to be incorporated into future interventions.